Transient deep ocean cooling in the eastern equatorial Pacific Ocean at the Eocene-Oligocene Transition - Taylor, Victoria; Wilson, Paul; Bohaty, Steven M.; Meckler, Anna N. (Paleoceanography and paleoclimatology, 2023)
At the Eocene-Oligocene Transition (EOT), approximately 34 million years ago, Earth abruptly transitioned to a climate state sufficiently cool for Antarctica to sustain large ice sheets for the first time in tens to hundreds of millions of years. Oxygen isotope records from deep-sea benthic foraminifera (δ18Ob) provide the foundation of our understanding of this pivot point in Cenozoic climate history. A deeper insight, however, is hindered by the paucity of independent deep-sea temperature reconstructions and the ongoing challenge of deconvolving the temperature and continental ice volume signals embedded in δ18Ob records. Here we present records of deep-sea temperature change from the eastern equatorial Pacific for the EOT using clumped isotope thermometry, which permits explicit temperature reconstructions independent of seawater chemistry and continental ice volume. Our records suggest that the deep Pacific Ocean cooled markedly at the EOT by 4.7 ± 0.9°C. This decrease in temperature represents the first direct and robust evidence of deep-sea cooling associated with the inception of major Cenozoic glaciation. However, our data also indicate that this major cooling of the deep Pacific Ocean at the EOT was short-lived (∼200 kyrs), with temperatures rebounding to values close to pre-EOT levels by 33.6 Ma. Our calculated record of seawater δ18O suggests that this rebound in ocean temperature occurred despite the continued presence of a large-scale Antarctic ice sheet. This finding suggests a degree of decoupling between deep ocean temperatures in the eastern equatorial Pacific Ocean and the behavior of the newly established Antarctic ice sheet.
Gesehen am 31.01.2024